Evaluation of self-healing performance of polyacrylamide/polyvinyl alcohol hydrogel using molecular dynamic simulation - Wong, Ming Zhen (2021)
In this study, the self-healing property of polyacrylamide/polyvinyl alcohol (PAM/PVA) hydrogel was examined using the molecular dynamic simulation. The Material Studio software was utilised to study the effect of temperature and hydrogel water content on the self-healing capability of the hydrogel. In the simulation, the hydrogel models with different water content were created. To evaluate how temperature affects the hydrogel’s self-healing capcity of the hydrogel, the hydrogel with 80% water content was run under different temperatures which are 273K, 298K, 323K, 348K and 398K. In order to study the effect of hydrogel water content on the self-healing property, the hydrogel water content were varied from 0%, 20%, 40%, 60% to 80%. The models with different hydrogel water content were run under room temperature which is 298K. All the models are examined in terms of diffusion coefficient which is determined using Mean Square Displacement (MSD) function, self-healing duration from the bilayer density and the molecular aggregation using Radial Distribution Function (RDF). After obtaining the diffusion coefficient of the hydrogel models with different water content at different temperatures, the activation energy and pre-exponential factor of the models are studied. The result shows that the self-healing performace of PAM/PVA hydrogel is enhaced by increasing the temperature and hydrogel water content.